2018
DOI: 10.1002/ece3.3785
|View full text |Cite
|
Sign up to set email alerts
|

Host species, and not environment, predicts variation in blood parasite prevalence, distribution, and diversity along a humidity gradient in northern South America

Abstract: Environmental factors strongly influence the ecology and evolution of vector‐borne infectious diseases. However, our understanding of the influence of climatic variation on host–parasite interactions in tropical systems is rudimentary. We studied five species of birds and their haemosporidian parasites (Plasmodium and Haemoproteus) at 16 sampling sites to understand how environmental heterogeneity influences patterns of parasite prevalence, distribution, and diversity across a marked gradient in water availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 106 publications
2
38
0
1
Order By: Relevance
“…2015). Additional interspecific variation may be explained by unique ‘species effects’ (e.g., Pulgarín-R et al . 2018; Ricklefs et al .…”
Section: Introductionmentioning
confidence: 99%
“…2015). Additional interspecific variation may be explained by unique ‘species effects’ (e.g., Pulgarín-R et al . 2018; Ricklefs et al .…”
Section: Introductionmentioning
confidence: 99%
“…more important for parasites vectored by Culicoides midges, the primary vectors of Haemoproteus(Kirkeby, Bødker, Stockmarr, & Enøe, 2009). However, a recent study of Amazonian birds did not find such a relationship(Pulgarín-R et al, 2018). Taken together, we therefore theorize that microhabitat differences largely explain the differences in infection rate observed between populations, while different immune responses may dictate interspecific differences in infection rate.Despite the fact that pied flycatchers have a significantly higher rate of blood parasite infections, the pattern of haemosporidian lineage diversity goes in the opposite direction.…”
mentioning
confidence: 46%
“…Areas near standing water are often important for determining prevalence of Plasmodium , which is most frequently mosquito‐borne (Wood et al, ), whereas damp and marshy ground is more important for parasites vectored by Culicoides midges, the primary vectors of Haemoproteus (Kirkeby, Bødker, Stockmarr, & Enøe, ). However, a recent study of Amazonian birds did not find such a relationship (Pulgarín‐R et al, ). Taken together, we therefore theorize that microhabitat differences largely explain the differences in infection rate observed between populations, while different immune responses may dictate interspecific differences in infection rate.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The fact that haemosporidian parasites need a vector for completing their cycle life extends the number of elements affecting prevalence of these parasites. Although some studies have shown limited or no relationship between climate and prevalence [34], some have showed that vector populations might increase their number due to climate change and, therefore, vector-borne infectious diseases may increase every year [35]. Vector availability might also change among seasons, thus, during spring the amount of vectors in the wild increase [36] raising the probabilities to become infected [37].…”
Section: Introductionmentioning
confidence: 99%